2014
DOI: 10.1016/j.proeng.2014.12.401
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of Multilayered Polyurethane Foam Core Sandwich Panels for Static Flexural Stiffness

Abstract: Light weight sandwich laminated panels are increasingly being used as structural materials for a wide variety of applications in marine, aerospace, automobile, transportation and electronic packing sectors. These sandwich panels are separated by stiff and strong face sheets, with low density core such as polyurethane foam, corrugated polyvinyl chloride sheets, aluminum honeycomb or polystyrene cellular solids. The core provides the necessary section modulus as well as shear rigidity at a low weight premium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The skin thickness effect was investigated by Kumar and Soragaon. 69 There were two different configurations, the first one was 1 mm glass fibre skins with 16 mm PU core and the other was 2 mm glass fibre skins with 18 mm PU core. Increasing skin thickness with similar core material resulted in two times higher bending stiffness.…”
Section: Core Shear and Face Sheet Ultimate Stressesmentioning
confidence: 99%
“…The skin thickness effect was investigated by Kumar and Soragaon. 69 There were two different configurations, the first one was 1 mm glass fibre skins with 16 mm PU core and the other was 2 mm glass fibre skins with 18 mm PU core. Increasing skin thickness with similar core material resulted in two times higher bending stiffness.…”
Section: Core Shear and Face Sheet Ultimate Stressesmentioning
confidence: 99%
“…They estimated that the threshold loading levels at infinite fatigue life were 23% and 37% of ultimate monotonic strength for the cases of fully reversed loading and fully unloaded conditions, respectively. Kumar et al [37] also studied the effect of change of thickness of fibre-reinforced polymer (FRP) facing sheets and inserts on the composite panels bending behaviour. They kept the total thickness of composite panels constant, while the span length was varying to find which combination of the panel, containing varied thickness of face sheets and inserts, could provide the best static flexural values.…”
Section: Bending and Shear Behaviourmentioning
confidence: 99%
“…Wang et al (2014) focused on the bending behaviour of an innovative sandwich panels with GFRP face sheets and a foam-web core (GFFW) panels, where t]heir experimental study demonstrated that the ultimate bending strength and initial bending stiffness can be significantly enhanced by increasing web thickness. Kumar and Soragaon (2014) studied on the effect of change thickness of fibre reinforced polymer (FRP) facing sheets and inserts on the flexural behaviour of sandwich panels with a constant total thickness. Tuwar et al (2015) evaluated three different polyurethane foam configurations for (GFRP) foam-core sandwich panels.…”
Section: Introductionmentioning
confidence: 99%